2021
DOI: 10.3389/fgene.2021.638244
|View full text |Cite
|
Sign up to set email alerts
|

Dicer1 Promotes Colon Cancer Cell Invasion and Migration Through Modulation of tRF-20-MEJB5Y13 Expression Under Hypoxia

Abstract: Hypoxia plays a key role in colorectal cancer (CRC) metastasis, but its underlying mechanism remains largely unknown. Dicer1, an RNase, has been considered as a tumor regulator in many tumors. However, whether Dicer1 affects CRC progression under hypoxia remains uncertain. In this study, we found that Dicer1 expression was induced by hypoxia in CRC cells and it mediates hypoxia-induced CRC cell progression. Furthermore, we found that the expression of tRF-20-MEJB5Y13, a small non-coding RNA derived from tRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…There were signi cant differences in the expression of different tRFs under hypoxic conditions. Among the differentially expressed tRFs, two signi cantly downregulated tRFs (tRF-20-M0NK5Y93, tRF-21-3OPP6N7KE) and one signi cantly upregulated tRF (tRF-20-MEJB5Y13) showed the most obvious expression differences, which were consistent with the trend of sequencing results (see the basis of previous work) [24,25]. All three types of tRFs are derived from tRNAs corresponding to different codons for arginine (Arg).…”
Section: Introductionsupporting
confidence: 87%
“…There were signi cant differences in the expression of different tRFs under hypoxic conditions. Among the differentially expressed tRFs, two signi cantly downregulated tRFs (tRF-20-M0NK5Y93, tRF-21-3OPP6N7KE) and one signi cantly upregulated tRF (tRF-20-MEJB5Y13) showed the most obvious expression differences, which were consistent with the trend of sequencing results (see the basis of previous work) [24,25]. All three types of tRFs are derived from tRNAs corresponding to different codons for arginine (Arg).…”
Section: Introductionsupporting
confidence: 87%
“…They are involved in the cell cycle, proliferation, cell apoptosis, and many other biological regulation pathways (15). Many pieces of literature reported that tRFs are actively derived from precursor RNAs and the 3' or 5' end-matching tRFs are largely cleaved by Dicer1 owing to their structural features (7,16). Meanwhile, considering the bind method between tRFs and mRNA of the target genes, Kuscu et al showed that Dicer-independent tRF-3s could suppress the posttranscription of genes by an Argonaute-RISC method, which had a certain degree of similarity with miRNAs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Its stable structure and high expression in body fluids make it relatively easy to detect, which makes it possible to become a new potential biomarker for tumors. Currently, most studies on tsRNAs have described the effects on proliferation, invasion, and migration of tumor cells and the mechanisms involved in hypoxia and epithelial to mesenchymal transformation (EMT) ( 10 , 21 , 51 , 52 ). However, there are few studies on whether tsRNAs can be used as a biomarker for tumors ( 18 , 24 , 53 ).…”
Section: Discussionmentioning
confidence: 99%